Maraval Water Works, Trinidad - (:unkn) unknown (Bonanza, Smith Bros and Co.,[Trinidad and Tobago], 2011)
The postcard shows the Maraval Reservoir which was first established in 1850s to provide pipe bourne water to Port of Spain and its environs by order of the then Governor, Lord Harris. Printed at the back of the postcard is an adverstisement for the Bonanza, department store which was located in Port of Spain in the early 1900s.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Reservoirs--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Maraval; Architecture--Trinidad and Tobago